(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Drug recycling is a sustainable approach to reducing pharmaceutical waste. This study compares the antimicrobial activity of expired and unexpired Azithromycin using the agar well diffusion method. Retained antibacterial efficacy in expired samples suggests potential for non-clinical reuse, while highlighting the need for further safety, stability, and effectiveness studies. Objectives: To compare the antimicrobial activity of expired and unexpired Azithromycin using the agar well diffusion method, evaluate retained antibacterial efficacy, and explore the potential of expired antibiotics for sustainable pharmaceutical waste management. Methodology: Sterile swabs were prepared and sterilized. Wells of 6 mm diameter were made aseptically. Antibacterial activity was tested using the agar well diffusion method on Muller Hinton Agar. Plates were inoculated with bacterial suspension and dried. Drug solutions (20 μl) were added into wells and incubated at 37°C for 24 hours. Zones of inhibition were measured to compare activity. Results: Expired and unexpired Azithromycin were tested against bacterial strains. Zones of inhibition showed comparable activity, with slight variations. Unexpired samples showed marginally higher inhibition in some cases. Both Gram-positive and Gram-negative bacteria responded similarly, indicating retained antibacterial efficacy. Conclusion: Expired Azithromycin shows potential for reuse in non-clinical applications, supporting sustainable waste management. Further studies are required to evaluate safety, stability, and effectiveness before practical implementation.